IMPROVEMENT OF SIMVASTATIN SOLUBILITY USING HPMCAS, LOCUST BEAN GUM, SODIUM ALGINATE AND TPGS AS A POLYMER WITH SOLID DISPERSION METHOD - SOPYAN, IYAN; KAMILAH, ZIRLY YUSRIANI; MEGANTARA, SANDRA; SRIWIDODO (International Journal of Applied Pharmaceutics, 2023)
Objective: Simvastatin (SV) is a cholesterol-lowering drug that classified in BCS (Biopharmaceutics Classification System) Class II class with high permeability but low solubility value. This study aims to obtain a solid dispersion formula that can increase the solubility of Simvastatin. HPMCAS, Locust Bean Gum, Sodium Alginate, and TPGS are four candidate polymers that will be selected by in silico study to make a solid dispersion formula. Methods: The solid dispersion was prepared with two polymers, Locust Bean Gum (LBG), which has no hydrogen bonds with Simvastatin, and Sodium Alginate (SA), which has hydrogen bonds with Simvastatin, made by the ratio of mass 1:1, 1:2, 1:3, 1:4. Materials were evaluated by solubility and dissolution studies, then characterized using FTIR, DSC, and PXRD. Results: Each drug-polymer ratio showed an increase in solubility and dissolution, but the SV-LBG formula (1:4) showed the largest increase, with a 4 folded increase in solubility and a roughly 2 folded increase in dissolution. The characterisation FTIR data demonstrate that the drug molecules are disseminated inside the polymer, and the PXRD diffractogram demonstrated a deacrease in crystallinity to the amorphous phase, and the DSC thermogram also demonstrated changes in thermal behavior. Conclusion: Solid dispersion is a promising method for increasing the solubility of simvastatin. The use of locust bean gum polymer was proven to increase the solubility and dissolution of simvastatin with the best formula SV-LBG (1:4).